Effects of pre-creep on the dislocations of 316LN Austenite stainless steel. (25th September 2017) - Pei, Hai-xiang; Hui, Jun; Hua, Hou; Feng, Zai-xin; Xu, Xiao-long
Abstract: The 316LN Austenite stainless steels (316LNASS) were pre-creep treated, the evolution of microstructure were investigated. The samples were pre-creep at 593 K and from 500 to 2000 h at 873 K with a stress in the range of 20 to 150 MPa, Then the evolution of microstructure and precipitation were investigated by optical microscope (OM), and transmission electron microscope (TEM). The results show that the crystal surface slipping resulted in dislocations and original dislocations decomposition during the pre-creep process, and generate quadrilateral or hexagonal dislocation network was obviously. The sub-grain boundary gradually became narrow with the increasing of pre-creep treatment time and temperature. When the pre-creep temperature was 593 K and 873 K, dislocation network gradually disappear with the increasing of pre-creep time and load. When the pre-creep temperature was 873 K under 120 MPa, and the treatment time was 2000 h, the hexagonal dislocation network (HDN) would completely disappeared. When the pre-creep temperature was 593 K under 20 MPa, and the treatment time was 500 h, the quadrilateral dislocation network (QDN) would completely disappeared.